2017
DOI: 10.1016/j.breast.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Total tumor load assessed by one-step nucleic acid amplification assay as an intraoperative predictor for non-sentinel lymph node metastasis in breast cancer

Abstract: Keywords:Breast cancer One-step nucleic acid amplification Sentinel lymph node Non-sentinel lymph node metastasis Axillary lymph node dissection Total tumor load a b s t r a c t Background: This study aimed to determine the relationship between CK19 mRNA copy number in sentinel lymph nodes (SLN) assessed by one-step nucleic acid amplification (OSNA) technique, and nonsentinel lymph nodes (NSLN) metastization in invasive breast cancer. A model using total tumor load (TTL) obtained by OSNA technique was also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…Peg et al first reported the concept of TTL, defined as the amount of CK19 mRNA copies in all positive SLNs, 25 and concluded that TTL was an independent predictor of NSLN metastasis by using multivariate analysis of tumor size, human epidermal growth factor receptor 2 (HER2), LVI, and the number of metastatic SLNs. The result was consistent with that reported by Nabais et al 27 TTL comprises two elements (the number and the size of SLN metastases), indicating that TTL can accurately estimate axillary tumor burden as one continuous variable. Moreover, the advantage of TTL as a predictive parameter is that TTL is automatized, reproducible, and can be assessed intraoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…Peg et al first reported the concept of TTL, defined as the amount of CK19 mRNA copies in all positive SLNs, 25 and concluded that TTL was an independent predictor of NSLN metastasis by using multivariate analysis of tumor size, human epidermal growth factor receptor 2 (HER2), LVI, and the number of metastatic SLNs. The result was consistent with that reported by Nabais et al 27 TTL comprises two elements (the number and the size of SLN metastases), indicating that TTL can accurately estimate axillary tumor burden as one continuous variable. Moreover, the advantage of TTL as a predictive parameter is that TTL is automatized, reproducible, and can be assessed intraoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, non-NSLN involvement could not be accurately evaluated in these patients. Second, the influence of total tumor burden and pathological tumor stage were not investigated, although these have been previously identified as useful predictors of non-NSLN metastasis 35-36 . …”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned studies include both micro‐ and macrometastatic cases as many predate the acceptance that micrometastatic disease does not warrant automatic ALND. Reviewing the literature, two studies have reported cutoffs for macrometastatic disease: Nabais 16 studied 58 patients with a TTL cutoff of 190 000 copies/µL (73.3% sensitivity; 74.4% specificity), and Fung 8 studied 122 patients and used a cutoff of 15 000 (sensitivity 0.815; specificity 0.908) to discriminate between >2 and <2 involved nodes in line with Z0011 practice. Future research should focus on macrometastatic disease given the aforementioned change in international practice.…”
Section: Discussionmentioning
confidence: 99%